The certification of the verifying archaeologist: towards a more efficient state and archaeology with higher professional standards - Cáceda Guillén, Daniel Eduardo (2026)
The public management of Archaeological Cultural Heritage (ACH) in Peru faces a structural efficiency challenge, manifested in administrative rigidity (over 50% of CIRAS files remain unresolved) and technical weakness (80% of projects are flagged with observations). The objective of this article is to propose the figure of the Verifying Archaeologist, a professional with certified labor competencies (MTPE), whose role as a Delegated Agent vested with Public Faith would optimize state management. The methodology was based on a Critical Documentary Analysis of key regulations (Legislative Decree 1680, Supreme Decree N° 011-2022-MC) to design an internal normative implementation framework. The results include the design of a three-phase implementation: 1) Officialization of Labor Competence Standards (ECL), encompassing technical mastery and Fundamental Ethical Commitment; 2) Modification of the Regulation on Archaeological Interventions to create the "Registry of Verifying Archaeologists" and establish their assignment through a public merit-based competition to guarantee independence of opinion; and 3) Issuance of a Sectoral Directive. It is concluded that the Verifying Archaeologist figure is viable through sectoral adjustments, allowing for the reduction of administrative turnaround times and the elevation of technical quality. This model transforms the Ministry of Culture (MINCUL) into a strategic regulatory entity that guarantees the protection of ACH.